Sequential water balance for Lagoa Seca - Paraíba – Brazil (Research, Society and Development, 2020)
The main socioeconomic activities in the municipality of Lagoa seca are related to family farming and the horticultural sector, which benefits from the characteristics of the region's soil and climate. Thus, the study aimed to carry out the calculation of the sequential water balance, aiming at verifying the oscillations of the climatic elements and determining and making available contributions for elaborations of rural, urban and agricultural planning. The monthly average rainfall data was characterized as a period of normal climatological, where, the software was used in electronic spreadsheets, to extract the values of the monthly and annual averages of the precipitation of the period from 1981 to 2019. The data of average temperature were estimated by the software Estima. Since the aforementioned municipality has no equipment to carry out such observation. The applied methodology was that of Thornthwaite & Mather for the computation of the sequential water balance. The BHS provides detailed knowledge of the climatic elements of the studied period, generating extraordinary information for government decision makers and for the elaborators of livestock, agricultural, agribusiness projects, for horticultural products, aiming at a sustainable development of the products in the studied area. The sequential water balance provided contributions to the analysis of the extreme values of the elements studied for the period from 1981 to 2019. The monthly evapotranspiration values for the municipality under study are linked to the geographic coordinates, mainly the orography. Soil compaction (urban and rural), vertical growth and the lack of afforestation close to the water table are increasing the evapotranspirastive power.